Carbonation investigation on atmospherically exposed lime-treated silty soil. (December 2022) - Das, Geetanjali; Razakamanantsoa, Andry; Saussaye, Lucile; Losma, Francesca; Deneele, Dimitri
Abstract: The effect of carbonation on a one-year atmospherically exposed lime-treated soil structure is investigated. The investigation involves analyzing the chemical characteristics and pore-structure modifications of several specimens sampled up to 12 cm depth perpendicular to the surface. On comparing the analysis with untreated and lime-treated core-sampled specimens, carbonation is found to have occurred on specimens sampled up to 4.2 cm depth perpendicular to the surface. The decrease in soil pH to a value 9 or lower than that and the presence of carbonates confirmed the carbonation effect. At the pore-structure level, carbonation mechanism is found to increase macropores of diameter 20000–100000 Å, which is missing in the non-carbonated specimens and even greater than the one found at untreated soil. Such an observation confirmed the loss of cementitious compounds due to carbonation, thus, converting the mesopores developed due to lime treatment to macropores of larger pore diameter.